Older Men with Dementia Are at Greater Risk than Women of Serious Events After Initiating Antipsychotic Therapy. Issue 1 (10th January 2013) - Rochon, Paula A.; Gruneir, Andrea; Gill, Sudeep S.; Wu, Wei; Fischer, Hadas D.; Bronskill, Susan E.; Normand, Sharon‐Lise T.; Austin, Peter C.; Seitz, Dallas P.; Bell, Chaim M.; Fu, Longdi; Lipscombe, Lorraine; et al.
<x xml:space="preserve">Abstract</x> Objectives To understand how drug therapy differently affects older women and men. Design Population‐based, retrospective cohort study. Setting Ontario, Canada. Participants Twenty‐one thousand five hundred twenty‐six older adults (13, 760 women, 7, 766 men) with dementia newly started on oral atypical antipsychotic therapy between April 1, 2007, and March 1, 2010. Measurements Numbers and rates of serious events. Serious events were defined as a hospital admission or death within 30 days of treatment initiation. Unadjusted and adjusted odds ratios of women and men were compared in the full cohort and in strata based on setting of care, age, Charlson Comorbidity Index (CCI), and antipsychotic dose. Results Of 21, 526 older adults with a median age of 84, 1, 889 (8.8%) had a serious event (1, 044 women, 7.6%; 845 men, 10.9%). Of these, 363 women (2.6%) and 355 men (4.6%) died. Men were more likely than women to be hospitalized or die during the 30‐day follow‐up period (adjusted odds ratio = 1.47, 95% confidence interval = 1.33–1.62) and consistently more likely to experience a serious event in each stratum. A gradient of risk according to drug dose was found for the development of a serious event in women and men. Conclusion The risk of developing a serious event shortly after the initiation of antipsychotic therapy was high in women and men with dementia but was consistently higher in older men. This pattern remained the same in strata based on setting of care, age, CCI, and antipsychotic dose.